ChemInform Abstract: An SiO2/ZnBr2 Mediated Expeditious Approach to 3‐Methyl‐1‐phenyl‐1H‐pyrazol‐5(4H)‐one Derivatives in Water under Microwave Irradiation. Issue 20 (April 2016) - Parveen, Mehtab; Azaz, Shaista; Malla, Ali Mohammed; Ahmad, Faheem; Ahmad, Musheer; Gupta, Mayank
Abstract: The one‐pot three‐component title reaction between ethylacetoacetate, phenyl‐ or 2, 4‐dinitrophenylhydrazine and various aryl or hetaryl aldehydes proves more practical, efficient and eco‐friendly than previously developed methods.